The Molecular Bacterial Load Assay Replaces Solid Culture for Measuring Early Bactericidal Response to Antituberculosis Treatment - Honeyborne, Isobella (American Society for Microbiology, 2014)
We evaluated the use of the molecular bacterial load (MBL) assay, for measuring viable Mycobacterium tuberculosis in sputum, in comparison with solid agar and liquid culture. The MBL assay provides early information on the rate of decline in bacterial load and has technical advantages over culture in either form.